Tensile and bending analysis of simplified 3D woven fabric modelled with finite element analysis / Farah Amira Sulaiman, Suzaini Abd Ghani and Mohamad Faizul Yahya - Sulaiman, Farah Amira; Abd Ghani, Suzaini; Yahya, Mohamad Faizul (Universiti Teknologi MARA (UiTM), 2022)
This paper presented the modeling of simplified 3D woven fabric in tensile and bending behavior. The modeling technique used to simulate woven fabric using finite element analysis and incorporated with Abaqus software. 3D means that the woven fabric features in software having three dimensions which are horizontal, vertical, and depth (x, y, and z) dimensions. The simplified 3D woven fabric model is treated with various parameters on modulus and mesh size to study realistic stress-strain and force-displacement fields. Therefore, the important detailed FEA for modeling woven fabric requires setting geometric parameters such as dimension fabric structures, loads, pressure, boundary conditions to simulate the successful assumption on the mechanical performance of the fabric. The model is first used to simulate tensile and bending under various modulus. Each simulation shows the highest modulus give the higher stress and lowest strain for tensile simulation and higher force and lowest displacement for bending simulation. In a second step, different mesh size has been added to the model with the same modulus, show the smaller mesh size gives the accurate analysis. The prediction results of tensile and bending simulation presented in strain-stress and force-displacement curve, respectively based on modulus and mesh size.